Compendium of Intra-African and Related Foreign Trade Statistics 2013 - United Nations (United Nations, 2014)
This publication is compiled to provide quality and timely statistical data for the monitoring, evaluation, analysis, research, and promotion of the intra-African trade. It is intended to serve the needs of researchers, policy makers, and the public who work on trade issues. This seventh edition of the Compendium presents foreign trade data in sixteen chapters for all African countries for the period 2004 to 2012. Information on total, share, direction, and evolution of African trade is provided. Focusing on intra-African trade, related statistical data of trade flows are grouped by region, subregions, and Regional Economic Communities (RECs) in Africa, a unique feature that has been found nowhere else. It is hoped that the Compendium will provide the needed support to ongoing efforts aimed at ensuring the integration of the African continent.